Sonographic Comparison of Atherosclerotic Changes in Carotid Arteries of Diabetic and Non-Diabetic Individuals - Zartash Gul, Anjum Tazeen, Syed Muhammad Yousaf Farooq, Irfan Shabbir, Mishal Asif, Syed Amir Gilani, Muhammad Kamran, Khalil Ur Rehman, Irfan Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the sonographic findings of atherosclerotic changes in carotid arteries of diabetic and non-diabetic individuals. Material & Methods: A cross-sectional study of 62 diabetic and non-diabetic individuals was conducted from 11 November 2021 to 20 March 2022 at the Radiology Department of District Head Quarter Hospital, Faisalabad, Pakistan. The ultrasound of carotid arteries with a TOSHIBA MX Doppler ultrasound machine, using a linear probe with transducer frequency of 5-12.5MHz was performed in both diabetic and non-diabetic participants. Results: The mean value of CIMT in diabetic patients was 0.6839 ± 0.29178mm while the mean value of CIMT in Non- diabetic patients was 0.8000 ± 0.08563mm. The mean value of peak systolic velocity (PSV) of CCA in diabetic patients was 41.4194 ± 6.60189mm and the mean value of PSV of CCA in Non- diabetic patients was 41.7742 ± 6.52538mm. The mean value of PSV of ICA in diabetic patients was 58.4839 ± 12.03293mm and in Non- diabetic patients was 59.0323 ±10.03489mm. Similarly, the mean value of ICA/CCA ratio in diabetic patients was 1.4097 ± 0.39442 while in non-diabetic patients was 1.4323 ± 0.30374. Conclusion: The diagnostic accuracy of ultrasonography of common carotid artery, and internal carotid artery is very high for atherosclerosis. The use of sonography for measurement of IMT and plaque area act as a vital tool for the detection of atherosclerosis changes due to diabetes. Keywords: carotid artery, diabetes mellitus, intima-media thickness